Displacement based seismic analysis for out of plane bending of unreinforced masonry walls. - Doherty, K. (Earthquake engineering & structural dynamics.)
This paper addresses the problem of assessing the seismic resistance of brick masonry walls subject to out of plane bending. A simplified linearized displacement based procedure is presented along with recommendations for the selection of an appropriate substitute structure in order to provide the most representative analytical results. A trilinear relationship is used to characterize the real nonlinear force displacement relationship for unreinforced brick masonry walls. Predictions of the magnitude of support motion required to cause flexural failure of masonry walls using the linearized displacement based procedure and quasi static analysis procedures are compared with the results of experiments and non-linear time history analyses. The displacement base procedure is shown to give significantly better predictions than the force based method.